Bryozoan statoblasts from lake sediments in Madagascar, including two new species - Wood, Timothy S.; Unger, Lilian Eva; Rasoamihaingo, Laurence (European Journal of Taxonomy, 2023)
Madagascar is a freshwater biodiversity hotspot, yet the current understanding of freshwater bryozoan diversity is limited. Using a dissecting microscope, bryozoan statoblasts were collected during macrofossil analysis of a sediment core, which was taken from Lake Sofia, Madagascar, in 2019. There was a peak in the abundance of statoblasts prior to 1900, with 67 statoblast valves found at 45.5 cm and a decline in more recent sediments. A subsample of 14 specimens was examined under a scanning electron microscope to determine species identification. One of the species found was Plumatella kinesis. Two new species, Plumatella tsimiheta sp. nov. and Plumatella sofiae sp. nov. were also found and described. These results show the potential of lake sedimentary bryozoan remains for categorising species presence and distribution. Although poor preservation was a limitation for identification, there is still value in having a historical record of past biodiversity, especially when species may no longer be extant. This study highlights the need for further research to better understand the status of these species and other potential new species of bryozoan in Madagascar.